Determinan Kemiskinan Di Indonesia Menurut Perspektif Pembangunan Islam Periode 2007-2021 - Asril, Rossyta; Eka Puteri, Hesi (Indonesian Journal of Islamic Economics and Business, 2024)
Poverty is a very difficult problem to be solved by both developed and developing countries. This research was conducted to see how if the distribution of zakat funds, economic growth has been allocated properly and appropriately can it reduce the number of poverty levels and what if unemployment decreases can it reduce the amount of poverty. The research method used is quantitative research with a total sample of 30 taken from the last 15 years using a semi-annual time series. The method of data collection was carried out using the publication documentation method from the BPS Indonesian 2022 and the Financial Report of the BAZNAS, then analyzed using a multiple linear regression model using Eviews software version 12. This study found that the distribution of zakat funds and unemployment had an impact on the level of poverty in Indonesia. Economic growth has no impact on poverty in Indonesia. This study recommends a strategy in reducing poverty by allocating productive zakat funds with the right target and improving community economic growth and reducing the number of unemployed by looking at human resources, namely by carrying out social empowerment to the community so that unemployment will be reduced, and will increase income and will impact on poverty.